Biochemical effect of 2,4-D in animals: meta-analytic review, and in vivo study through trophic route - Hernandéz, Hilda Vanessa Poquioma (2020)
The 2,4-D is one of the most important agrochemical in Brasil, since its use increased with the development of 2,4-D resistant crops to the large monocultureover. However, its effect on non-target species is still under study. There are many research studying the effect of 2,4-D in the body, however all of them use different species of a large range of age, applying the xenobiotic by different routes and using many tissues to analyze the effect of 2,4-D on the enzymatic activity. In some of them, the agrotoxic is applied in combination with other compounds using high concentration for few hours, while in others are used more dilute concentrations of the herbicide pure, for several months. All this information makes it difficult the understanding of the real effect of 2,4-D over the oxidative stress. In order to disentangle all this information, it was don a meta analytici study and an in vivo study in fish. In the first part of this research it was studied the response of CAT, SOD, GST, GST, GR, GPx, and the level of GSH in organisms exposed to 2,4-D, in order to determine if variables such as phylogenetical group, age, exposure route, tissue of study, mixture with other compounds, dose applied and exposure time would be influencing the activity of action of those molecules, as a way to provide more conclusive information.In the second part, Rhamdia quelen was exposed to 2,4-D and there were assessed the same biochemical biomarkers from the fist part. In the meta analytical study it was found a clear difference in the response pattern from mammals and no-mammal animals. In the first group it seen a decrease in the activity of SOD and CAT, while in the second group the opposite is appreciated. The mixture with other additives is not a differential factor, while the age is a factor still unclear, studies using young animals were sparse. The hydric exposure causes increase in CAT, SOD and GST activity, while the oral one a drop in the activity of CAT, SOD, GPx and in the level of GSH. The response of the enzymatic and non-enzymatic molecules differs within the tissues however it is clear that male reproductive organs are more sensible regarding female organs. Finally, while the doses exposition is not determinant factor to increase or decrease the enzymatic activity, as longer the exposition time, lesser the activity of CAT, SOD and GPx is seen, while the GSH increases in larger exposition periods. From the in vivo study, there was found no oxidative stress in R. quelen exposed to doses of 20, 200 and 2000µg/kg for a period of 22 and 42 days. From these last results, corresponded with the data found in the first part of this investigation. Oxidative stress was not determined since the exposure occurred for a short period of time.